Details in hand :|how does gesturing relate to autobiographical thinking? - Acar, Naziye Güneş. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
Gestures and speech have different expressive capabilities. When narrating an autobiographical memory, gesturing may reduce the cognitive load of verbal reporting, gestures may function as externalized cues activating episodic details of the memory representation, or gestures might help the construction of event scenes experienced during the original event. Thus, gestures might have a mnemonic role in the retrieval of episodically and phenomenologically rich memories and this potential role might change as a function of age, reflecting the developmental differences in gesturing, memory, and related cognitive systems. Additionally, the use of gestural and verbal modalities, either separately or simultaneously, might vary with age and the episodicity of the information recalled. Using the cue-word technique, 35 children and 46 adults were asked to recall and verbally report six memories, then they rated the recalled memories on three phenomenological properties: visual imagery, spatial imagery, and reliving. Episodic, visuo-motoric and nonepisodic details of autobiographical memories and representational gestures produced during memory narration were coded from video-records. In adult memories, representational gesture production was associated with the recall of more episodic as well as visuo-motoric details, but not with the recall of non-episodic details. However, gesturing did not relate to the phenomenological experience of autobiographical memories via the number of details remembered. When narrating autobiographical events, adults preferred to use gestural and verbal modalities together, whereas children exclusively used the verbal modality. The modality preference of each group was more pronounced when reporting episodic details.
Keywords: Gesture -- Psychological aspects.; Narration (Rhetoric) -- Psychological aspects.; Autobiographical memory.